2020
DOI: 10.1080/0284186x.2020.1821089
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to international recommendations in the governance and organisation of Nordic cervical cancer screening programmes

Abstract: Introduction: Screening has been the primary reason for the decline in the incidence and mortality of cervical cancer in the Nordic countries since the beginning of screening in the 1960s. Recently, the incidence of cervical cancer has increased in the Nordic countries indicating the need to look closely at possibilities for further improvement in screening. This article provides an overview of cervical cancer screening programmes in the Nordic countries and whether the programmes adhere to international recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Cervical cancer screening programmes have always differed in various ways. For example, on one hand, Norway, Sweden, Italy, the UK, 12,13 and Australia 14 have introduced population-based screening programmes with organised call-recall systems relying on registries for information on the women's previous screening history. On the other hand, countries such as Japan and Germany do not have national screening registries and instead operate on an opportunistic basis.…”
Section: Relevance Of Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical cancer screening programmes have always differed in various ways. For example, on one hand, Norway, Sweden, Italy, the UK, 12,13 and Australia 14 have introduced population-based screening programmes with organised call-recall systems relying on registries for information on the women's previous screening history. On the other hand, countries such as Japan and Germany do not have national screening registries and instead operate on an opportunistic basis.…”
Section: Relevance Of Contextmentioning
confidence: 99%
“…13,15 Some programmes have mainly offered screening through primary care, whereas others have delivered it through specialist services, such as gynaecology. 12,16 Some programmes have started replacing cytology with HPV testing as the primary screening method. This approach has affected the laboratory landscape; for example, HPV testing is completed in an automated way that allows for economies of scale and larger laboratories with smaller workforces.…”
Section: Relevance Of Contextmentioning
confidence: 99%
“…The current CC screening programs in the Nordic countries included in this study are summarized in Table 1. Further details on screening programs can be found from a recent article on Nordic CC screening programs, 13 from fact sheets on the NordScreen website (nordscreen.org), and from national documentation. 5,14,15…”
Section: Settingmentioning
confidence: 99%
“…The guidelines also recommend that the percentage of uterine cancer deaths with known topography should be at least 80%. A comparison of Nordic cervical screening programs showed that Nordic countries, except Finland, fail to adhere to this recommendation 5 …”
Section: Introductionmentioning
confidence: 99%
“…A comparison of Nordic cervical screening programs showed that Nordic countries, except Finland, fail to adhere to this recommendation. 5 Methods exist to correct mortality by reallocating U-NOS to either cervix uteri or corpus uteri. Earlier studies have shown that reallocating U-NOS deaths increases mortality from both cancers.…”
Section: Introductionmentioning
confidence: 99%